ANALISIS SISTEM REKRUTMEN DAN SELEKSI AGEN PADA PT. ASURANSI JIWASRAYA (PERSERO) CABANG PEKALONGAN - Edy Purwanto; Nidya Novebriana (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2019)
Human resources have a very important role in every activity of the company. Human resources itself is a determinant of the effectiveness of the activities within the company. Although the company has been supported by facilities and infrastructure and sufficient funding sources, without the support of quality human resources, the company's activities will not run well and smoothly. The first step that becomes the main key to obtaining quality human resources is the recruitment and selection process to recruit and select workers that are suitable for the company's needs. This type of research is used to analyze the process of implementing recruitment and selection of new agents at PT. Asuransi Jiwasraya (Persero) Cabang Pekalongan is a descriptive study using a qualitative approach, in this study analyzing how the recruitment process and selection to get agents. The technique used in this study is to use interview techniques. The results of the research on the method and process of implementing recruitment and selection in general have been well implemented, what is also applied is also applied. In recruitment, you should increase the number of relationships and take advantage of online media owned by registered employees and agents in order to reduce costs and for selection there should be additional psychological tests to find out measuring or testing personality or temperament, talent, interest, intelligence and achievement desires from potential new agents